Helicobacter pylori biomimics for gastric-targeted drug delivery - Hage, N. (2016)
Drugs that are preferentially absorbed through the stomach or the small intestine have a narrow time window for absorption since passage through this region of the gastrointestinal tract is rapid. A drug delivery system that can adhere to the gastric epithelium will substantially slow down drug transit and help overcome this problem. To achieve this, this study proposes the novel use of a glycan-binding adhesion protein from Helicobacter pylori, BabA, to create targeted drug delivery vectors that can mimic the attachment of this bacterium to the gastric epithelium.